Inflation starts in Latin America and the Caribbean - Lewis Bynoe, Denny (Central Bank of Barbados [St. Michael]BB, 2007)
Attempts to identify the factors that initiate the high rates of inflation episodes in Latin America and the Caribbean (LAC) by using observations on 31 LAC countries between 1970 and 2006.